Non-randomness of exponential distance relation in the planetary system: An answer to Lecar. Issue 10 (15th November 2017) - Pletser, Vladimir
Highlights: The planet distance distribution cannot be similarly obtained by sequences of random numbers. The assumption of similar representation of planetary distances by random numbers is incorrect. Planet "closeness not too close" condition necessary but not sufficient to explain distance ratios. Abstract: One of the usual main objections against attempts in finding a physical cause for the planet distance distribution is based on the assumption that similar distance distribution could be obtained by sequences of random numbers. This assumption was stated by Lecar in a short article of 1973 that is still referred to nowadays. We show here how this assumption is incorrect.